2016
DOI: 10.1016/j.molcatb.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Screening of fungi from the genus Penicillium for production of β- fructofuranosidase and enzymatic synthesis of fructooligosaccharides

Abstract: Eight new isolated fungi of the genus Penicillium were evaluated for ␤fructofuranosidase (FFase) production. From these, Penicillium citreonigrum was selected for FFase and fructooligosaccharides (FOS) production. The influence of temperature, yeast extract concentration, pH and fermentation time on the FFase activity when using the whole microorganism was evaluated by 2 4 and 2 3 designs. The pH was set at 6.5 and no yeast extract was used in the optimization experiments since both shown low significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The potential of eight strains from the Penicillium genus, previously reported by Nascimento et al (2016) as β-fructofuranosidase producers, were herein tested for their ability to produce FOS, namely Penicillium aurantiogriseum URM 5139, Penicillium citrinum URM 2725, Penicillium commune URM 4939, Penicillium aurantiogriseum URM 5126, Penicillium implicatum URM 5426, Penicillium citreonigrum URM 4459, Penicillium glabrum URM 4757, and Penicillium islandicum URM 5073). All strains were obtained from the Micoteca of the Federal University of Pernambuco (URM -UFPE) and maintained at 4°C on Czapek Dox Agar medium (CZ) (Himedia, India).…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential of eight strains from the Penicillium genus, previously reported by Nascimento et al (2016) as β-fructofuranosidase producers, were herein tested for their ability to produce FOS, namely Penicillium aurantiogriseum URM 5139, Penicillium citrinum URM 2725, Penicillium commune URM 4939, Penicillium aurantiogriseum URM 5126, Penicillium implicatum URM 5426, Penicillium citreonigrum URM 4459, Penicillium glabrum URM 4757, and Penicillium islandicum URM 5073). All strains were obtained from the Micoteca of the Federal University of Pernambuco (URM -UFPE) and maintained at 4°C on Czapek Dox Agar medium (CZ) (Himedia, India).…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%
“…However, similar effects might be found to lower temperatures. Thus, the working temperature is an important parameter of the fermentation process, especially when working with the whole-cells of fungi, since it influences not only the product formation, but also the spore germination and the microorganism growth itself (Nascimento et al, 2016). Results found in the present work, concerning the evaluation of temperature on FOS production, are in agreement with the findings of other authors while using an Aspergillus japonicus strain (Mussatto et al, 2013), where temperatures between 26 and 30°C were found to raise FOS production, while temperatures above 30°C had an opposite effect.…”
Section: Optimization Of Fos Production In Shake Flasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial preparations of enzymes from strains of Aspergillus aculeatus (Pectinex Ultra SP‐L and Viscozyme L) and Aspergillus niger (Rohapect CM), with high transfructosylating activity have been successfully used to synthesize FOS. Moreover, studies involving the production of FFases were already reported using Aspergillus japonicus , A. niger and other filamentous fungi, such as Penicillium oxalicum , Penicillium citreonigrum , Penicillium sizovae , and Cladosporium cladosporioides , the last two standing out in the production of neo‐FOS and the last one in that of FOS using seawater . Nonetheless, there is a strong need to further explore the Aspergillus genus diversity to identify new strains able to overproduce these enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The attainment of FOS yields higher than 55-60% is still a challenge due to enzyme inhibition by the products released during FOS synthesis (Sangeetha, Ramesh, & Prapulla, 2005). Consequently, several researchers continue to pursue new and optimized conditions towards higher FOS production yields such as the use of whole cells, instead of purified enzymes (Castro, Nobre, Duprez, De Weireld, & Hantson, 2017;Dominguez et al, 2012;Nascimento, Nobre, Cavalcanti, Teixeira, & Porto, 2016;Nobre et al, 2016) and the use of new isolated strains such as the Aspergillus ibericus MUM 03.49, an isolate from Portuguese wine grapes (Nobre et al, 2018), duly characterized, with great potential for FOS production. As a result, current studies are not only focused on the physicochemical characteristics of the new FOS produced by these microorganisms, but also on their prebiotic index.…”
Section: Introductionmentioning
confidence: 99%